Association between Age Related Macular Degeneration and Anxiety Disorder - Anugerah Ramadhan Putra (Sriwijaya Journal of Ophthalmology, 2020)
Anxiety disorders has been termed a social epidemic especially by people with disabilities, one of them is visual impairment because age related macular degenaration. The present study compared the qualitative dimensions of loneliness of the blind and visually impaired with the generall population not on the frequency or intensity of their loneliness. This study compared the qualitative dimensions of loneliness between blind and visually impaired persons and the general population, rather than the frequency or intensity of their loneliness., no studies have specifically evaluated anxiety disorder in young and middle-aged people with visual impairment (VI). High prevalence of loneliness among the visually impaired elderly persons, that reports a prevalence of 54% in the visually impaired elderly aged ≥55 years. In addition, the risk of loneliness was higher for those who were aged 36 to 50 years, exposed to bullying or physical or sexual abuse, had blindness, other impairments, or were unemployed. The mean score for loneliness was 4.83 (SD 1.82), 4.88 for women and 4.78 for men (p = 0.46). The majority of participants reported missing somebody to be with sometimes (39.0%) or often (21.1%). The prevalence of anxiety among older adults with AMD is also higher than among both general populations of older adults and those with other common age-related medical conditions. The aim of this study to estimate the prevalence of loneliness and associated factors in adults with age related macular degeneration.